Relationship between patients' and clinicians' assessments of health status before and after knee arthroplasty. Issue 6 (1st July 2010) - Bream, Elizabeth; Charman, Susan C; Clift, Ben; Murray, David; Black, Nick
Abstract : Introduction: The use of patient reported outcome measures (PROMs) for four elective operations is mandatory in the English NHS from April 2009. In view of some scepticism by some clinicians as to the validity of PROMs, our aim was to explore the relationship between patients' and clinicians' reports of health status before and after knee arthroplasty. Methods: A secondary analysis of linked data from the Knee Arthroplasty Trial (patients' reports using the Oxford Knee Score) and the Tayside Arthroplasty Audit (clinicians' reports using the American Knee Society Score—Knee Score and Functional Score) was carried out. Correlations of scores were obtained for 284 patients before and 226 patients after surgery. Results: There was a moderately strong correlation between patients' and clinicians' views 1 year after surgery: Oxford Knee Score (OKS) versus American Knee Society Scores (AKSS) Knee Score r=−0.64; OKS versus AKSS Functional Score r=−0.44. Before surgery, the correlation between the OKS and the AKSS Functional Score was also moderate (r=−0.55) but was weak with the Knee Score (r=−0.23). There was no systematic direction to the differences between patients' and clinicians' assessments; patients were just as likely to report better health than their clinician as to report worse health. Discussion: Patients' postoperative assessments following knee arthroplasty, as regards their symptoms and disability, are practical to collect and can make a meaningful and useful contribution in routine use. In view of the advantages of collecting data on symptoms and disability directly from patients—lower cost, higher response rates, avoidance of systematic biases—confirmation of a moderately strong association with clinicians' views offers further reassurance for the routine use of PROMs, at least with knee arthroplasty.